Penguatan Nilai Etika dan Moral Melalui Sosialisasi Anti Bullying : Studi Kasus SD Negeri 02 Desa Banyuurip - Adhi Prasojo Rahman; Nurul Zuhroh; Arina Fahma; Milda Fatia Rahma; Maulida Nur Tazkia; Rijal Zultianda; M. Alfarabi Baihaqi; Ana Zahrotun Nihayah (Jurnal Pelayanan Masyarakat, 2024)
Bullying is a phenomenon that has become a global concern in recent decades. This problem is not limited to one country or culture, but is widespread throughout the world, reaching various levels of society, including in educational environments. The purpose of this implementation is to improve the ability and awareness of bullying and also children's literacy interests at SDN 2 Banyuurip. There are 3 methods used in this implementation, namely: preparation stage, assessment stage, program implementation stage. With this anti-bullying socialization at SDN 02 Banyuurip Village which can help reduce bullying behavior in the educational environment, teaching about empathy and respect for differences can help children understand and respect each other. Social relationships between are often closer because they grow up in small communities. Peer pressure can affect children's behavior, both in terms of bullying and positive attitudes. building supportive and inclusive social groups can help minimize bullying.